1975
DOI: 10.1001/archpedi.1975.02120460083020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Rib Fractures Due to Physiotherapy in a Neonate With Hyaline Membrane Disease

Abstract: ceed the elite and British groups. In short, these apparently plump arms contained not only fat but fluid not otherwise obvious on clinical exami¬ nation. The implications of this find¬ ing in terms of bodily growth, intel¬ lectual alertness, and, above all, resistance to infection are only too obvious and are manifested in the high incidence, morbidity, and mor¬ tality from infections and the rapid¬ ity with which these children can be triggered off into clinical malnutri¬ tion syndromes.There is, then, a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
6
0
3
Order By: Relevance
“…Coupage has been associated with pulmonary atelectasis in dogs and gastroesophageal reflux, multiple rib fractures, and brain lesions in infants . In the present study, PSE and AC showed no adverse events, even in dogs with coagulation disorders, although the number of enrolled dogs was relatively small and further evaluation will be needed to fully determine the potential adverse effects of these techniques.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Coupage has been associated with pulmonary atelectasis in dogs and gastroesophageal reflux, multiple rib fractures, and brain lesions in infants . In the present study, PSE and AC showed no adverse events, even in dogs with coagulation disorders, although the number of enrolled dogs was relatively small and further evaluation will be needed to fully determine the potential adverse effects of these techniques.…”
Section: Discussionmentioning
confidence: 63%
“…Numerous studies have also demonstrated the potential adverse effects of various CP maneuvers, mostly in very small and fragile patients. In human infants, there is an increased risk of gastroesophageal reflux and hemoglobin desaturation, potentially severe hypoxemia, rib fractures, and brain damage . However, most of these studies are based on percussion and vibration techniques …”
Section: Introductionmentioning
confidence: 99%
“…Percussion has been shown to cause an increase in hypoxemia (Falk et al 1984), but, when combined with thoracic expansion exercises, no fall was seen in oxygen saturation (Pryor et al 1990). Rib fractures were reported in a neonate (Purohit et al 1975). Vibration augments the expiratory flow and may help mobilize mucus (McCarren and Alison 2006).…”
Section: Percussion and Vibrationmentioning
confidence: 99%
“…Clinical experience suggests that these interventions are hardly effective on the big and stiff chest of the adult, whereas the compliant chest of the newborn and infant seems to provide for a high effectiveness of conventional CPT. The disadvantage of this difference is that this small chest can also be damaged more easily as suggested by reports on physiotherapy inflicted rib fractures in newborn infants [76].…”
Section: Avoiding Harmmentioning
confidence: 99%